1993
DOI: 10.1597/1545-1569(1993)030<0343:cmocww>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Morphology of Children with Williams Syndrome

Abstract: Facial dysmorphology is considered to be a major diagnostic feature in patients with Williams syndrome (WS). The dysmorphology is composed of soft tissue and skeletal components. In this study the skeletal component of the facial dysmorphology was examined by analyzing the lateral cephalometric radiographs of 8 children with WS. Seven anatomic areas were judged by means of the analysis of 48 cephalometric variables. Four skeletal features contributed to the facial appearance of children with WS: (1) the anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 17 publications
1
17
2
Order By: Relevance
“…For example, the retrognathic facial profile characteristic of Cretinism, Turner syndrome, and Down's syndrome is due to reduced cranial base length (Israel et al, ; Jensen, ; Rongen‐Westerlaken et al, ; Midtbo et al, ; Andersen et al, ; Quintanilla et al, ). Similar trends are also identified in Klinefelter syndrome and Williams's syndrome (Mass and Belostoky, ; Brkic et al, ). Given the function of cranial base in mid‐facial bone development, it is possible that the severely affected cranial base observed in the Evc2 global mutant mice leads to the shortened nasal and frontal bones during the early skull development.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the retrognathic facial profile characteristic of Cretinism, Turner syndrome, and Down's syndrome is due to reduced cranial base length (Israel et al, ; Jensen, ; Rongen‐Westerlaken et al, ; Midtbo et al, ; Andersen et al, ; Quintanilla et al, ). Similar trends are also identified in Klinefelter syndrome and Williams's syndrome (Mass and Belostoky, ; Brkic et al, ). Given the function of cranial base in mid‐facial bone development, it is possible that the severely affected cranial base observed in the Evc2 global mutant mice leads to the shortened nasal and frontal bones during the early skull development.…”
Section: Discussionmentioning
confidence: 99%
“…1,4 Regarding dental anomalies, Axelsson et al 9 Some previous studies have reported that the anterior cranial base is shorter than the norm in Caucasian patients with WS. 2,18 In contrast, Axelsson et al 19 reported that the anterior cranial base of female patients with WS was shorter than the norm, and the posterior cranial base was shorter than the norm irrespective of sex in Nordic patients with WS. Moreover, the cranial base angle was the same as the norm in patients with WS.…”
Section: Dental and Other Anomaliesmentioning
confidence: 96%
“…4,[9][10][11][12][13][14][15] The maxillofacial morphology of patients with WS is characterized by retrognathia or micrognathia, a pointed chin that indicates a deficiency of the chin button (pogonion to N-B line), a steep mandible, 1,2,4,14,16,17 maxillary protrusion, and labial inclination of the lower incisor. 13 Additionally, the cranial morphology of patients with WS is characterized by short anterior-posterior cranial base 2,14,18 and thickening of the frontal and occipital bones. 19 However, the findings regarding the dentocraniofacial morphological features of WS remain inconsistent.…”
mentioning
confidence: 99%
“…Cephalometric analysis has been used previously in the diagnosis of WS, but both prognathia and retrognathia were seen in WS patients, and common skeletal components were not dominant enough to characterize the facial dysmormphology [12]. It was therefore concluded that cephalometry is of little use [12,13]. We found dental aplasia in our WS patients much more frequently than Hertzberg et al in a previous American study [12].…”
Section: Discussionmentioning
confidence: 53%